Effects of Interseeding Ladino Clover into Tall Fescue Pastures of Varying Endophyte Status on Grazing and Subsequent Finishing Performance of Stocker Steers - L. W. Lomas; J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2020)
Two hundred fifty-six yearling steers grazing tall fescue pastures were used to evaluate the effects of fescue cultivar and interseeding ladino clover on available forage, grazing gains and subsequent finishing performance in 2016, 2017, 2018, and 2019. Fescue cultivars evaluated were high-endophyte ‘Kentucky 31,’ low-endophyte Kentucky 31 ‘HM4,’ and ‘MaxQ.’ In 2016, 2018, and 2019, steers that grazed pastures of low-endophyte Kentucky 31, HM4, or MaxQ gained significantly more (P<0.05) and produced more (P<0.05) gain/a than those that grazed high-endophyte Kentucky 31 pastures. Gains of cattle that grazed low-endophyte Kentucky 31, HM4, or MaxQ were similar (P>0.05). In 2017, steer gains were similar (P>0.05) among all cultivars. High-endophyte Kentucky 31 pastures had more (P<0.05) available forage than low-endophyte Kentucky 31, HM4, or MaxQ pastures during both 2016 and 2017. Steer gains and gain/a were similar (P>0.05) between pastures fertilized with nitrogen in the spring and those interseeded with ladino clover during all four years. Fescue cultivar or legume treatment had little effect on finishing performance or carcass characteristics of steers grazed in 2016, 2017, or 2018. Steers that grazed high-endophyte Kentucky 31 in 2016 or 2018 had lower (P<0.05) final finishing weight and lower (P<0.05) carcass weight than those that grazed low-endophyte Kentucky 31, HM4, or MaxQ. In 2017, steers that grazed pastures interseeded with ladino clover had lower (P<0.05) finishing gains and greater (P<0.05) feed:gain than those that grazed pastures with no legume.
Keywords: tall fescue; ladino clover; interseeding; endophyte; grazing; subsequent finishing performance